Valorization of Chicken Feather Waste in west Java into Bokashi Fertilizer Using Anaerobic Fermentation to Support Circular Agriculture: A Review - Agung Saputra, Satria; Zain, Faatin Nisriinaa; Pratiwi, Kharisma Ardhani Nur (Journal of Clean Technology, 2025)
The rapid growth of the poultry industry in Indonesia, particularly in West Java, has resulted in significant chicken feather waste, which remains largely unutilized and poses environmental risks due to its high keratin content. This review explores the potential of converting chicken feather waste into bokashi fertilizer through anaerobic fermentation as a sustainable strategy in line with circular agriculture principles. The fermentation process involves pretreatment using keratinase producing microorganisms such as Bacillus subtilis or Pseudomonas aeruginosa, followed by the application of Effective Microorganisms (EM4) activated with molasses. Under optimal conditions, including a carbon to nitrogen ratio of 25 to 30 to 1, temperature between 30 to 40 degrees Celsius, and humidity around 50 percent, the process can produce high quality organic fertilizer that meets national standards. The resulting bokashi exhibits favorable physical and chemical characteristics, such as high nitrogen content and a balanced nutrient profile. More broadly, this approach offers a low cost, scalable, and environmentally friendly solution for managing livestock waste while enhancing soil fertility and supporting regenerative farming. With further optimization and wider implementation at the community level, chicken feather based bokashi has strong potential to contribute to sustainable agriculture and effective waste management in poultry producing regions.